Perinatal mental disorders and suicidal risk among adolescent mothers living in urban areas of Cameroon - Miafo, Joël Djatche; Nzebou, Daniel; Stoll, Beat; Yimga Ngambia, Joris Cathel; von Overbeck Ottino, Saskia; Moayedoddin, Amir (Frontiers in Psychiatry, 2024)
Background In sub-Saharan Africa the birth rate among teenage mothers is the highest in the world. In 2021, there would be 6,114,000 births for 15–19-year-olds in this part of the world. In Cameroon, the fertility rate among adolescents aged 15–19 is 24%. However, there is a significant lack of data on the mental health of teenage mothers. Given the biopsychosocial conditions of the perinatal period and adolescence, we hypothesise that the prevalence of mental disorders and the risk of suicide is very high in Cameroon. The aim is therefore to determine the prevalence of perinatal mental disorders and suicide risk among adolescent mothers in urban areas of Cameroon. Methods Following ethical approval of the submitted protocol, we recruited adolescent mothers and data were collected using diagnostic interviews based on the DSM-5, PDM-2 and MINI guidelines. The types of sampling used were typical and incidental. Data were tabulated with Epidata 3.1 and processed with SPSS 25. Results 66.4% of adolescent mothers were diagnosed with a mental disorder and 27.4% with suicidal risk. It was found that there was a link between mental disorders and suicidal risk (p<0.001), with mothers at suicidal risk having an 8.4 times greater risk of having a mental disorder (OR=8.423). Linear regression confirmed the statistically significant relationship between perinatal mental disorders and suicidal risk. 31.1% of the total variance in suicidal risk was explained by mental disorders. The regression coefficients for mental disorders with a p<0.05 value is: perinatal depression (-0.279), post-partum psychosis (-0.133), trauma disorder (-0.034), generalised anxiety disorder (-0.008) and conduct disorder (-0.020). Conclusions Our hypothesis is confirmed, because the prevalence of 66.4% of mental disorders and 27.4% of suicidal risk are significantly high in Cameroon. In some way, the disorders predict suicidal risk, because the less an adolescent mother has one of these pathologies during the perinatal period, the less she will be at risk of suicide. More research of this kind is needed to contribute in providing more data, including solutions to address the morbidity and mortality problems associated with the mental health of teenage mothers.